2023
DOI: 10.1002/anie.202304202
|View full text |Cite
|
Sign up to set email alerts
|

Chalcogen‐Bond‐Induced Double Helix Based on Self‐Assembly of a Small Planar Building Block

Abstract: As a rule, helical structures at the molecular level are formed by non‐planar units. This makes the design of helices, starting from planar building blocks via self‐assembly, even more fascinating. Until now, however, this has only been achieved in rare cases, where hydrogen and halogen bonds were involved. Here, we show that the carbonyl‐tellurium interaction motif is suitable to assemble even small planar units into helical structures in solid phase. We found two different types of helices: both single and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…In contrast, σ-holes are present in the Se atom. Se is conjugated both with phosphonium and phenyl 33 which may serve as PnB donors. The P−O distance was measured as 2.47 Å, which is shorter than the sum of their van der Waals radii of O (152 pm) and P (180 pm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, σ-holes are present in the Se atom. Se is conjugated both with phosphonium and phenyl 33 which may serve as PnB donors. The P−O distance was measured as 2.47 Å, which is shorter than the sum of their van der Waals radii of O (152 pm) and P (180 pm).…”
Section: Resultsmentioning
confidence: 99%
“…It implies the ChB donor preferably adopts one major electrophilic region to interact with carboxylates. The phosphonium with phenyl groups possesses σ-holes based on the previous reports, which may serve as PnB donors. The P–O distance was measured as 2.47 Å, which is shorter than the sum of their van der Waals radii of O (152 pm) and P (180 pm).…”
Section: Resultsmentioning
confidence: 99%
“…1−5 Akin to halogen-bonding interactions, 6,7 ChB interactions have been considered to be a subclass of "σ-hole interactions" and intensively investigated from both experimental and theoretical aspects. 4,5,8−10 As such, the widespread applications of chalcogen bonding interactions range from recognition, sensing, extraction, and transport of anions 11−15 to crystal engineering, 4,16 supramolecular self-assembly, 17,18 materials chemistry, and drug design 8,19,20 as well as ChB-involving catalysis. 10,21−26 To our knowledge, the chalcogen atoms most frequently involved in chalcogen bonding are Te and Se, with S being less common.…”
mentioning
confidence: 99%
“…As an emerging class of noncovalent interactions, chalcogen bonding (ChB), the weak interaction between a covalently bonded electron-poor chalcogen (Te, Se, S) and an electron-rich Lewis base, has attracted growing interest from the chemical community and beyond over the past 20 years. Akin to halogen-bonding interactions, , ChB interactions have been considered to be a subclass of “σ-hole interactions” and intensively investigated from both experimental and theoretical aspects. ,, As such, the widespread applications of chalcogen bonding interactions range from recognition, sensing, extraction, and transport of anions to crystal engineering, , supramolecular self-assembly, , materials chemistry, and drug design ,, as well as ChB-involving catalysis. , To our knowledge, the chalcogen atoms most frequently involved in chalcogen bonding are Te and Se, with S being less common. , ,, Nonetheless, as the most electronegative chalcogen, oxygen has generally been viewed to be unable to form chalcogen bonding interactions, with only few computational exceptions. , Oxygen-centered chalcogen bonds remain puzzling and are largely unexplored.…”
mentioning
confidence: 99%
“…29,30 Coincidentally, Haberhauer and co-workers further demonstrated that supramolecular helices can be built by O⋯Te ChB between individual building units. 31 It is widely known that XB is based on a region of lower electron density (the so-called σ-hole) in which the potential is frequently positive, mainly in heavier halogens. The essence of XB is the attractive interaction between this region and an electron-rich site.…”
mentioning
confidence: 99%